Pectin Methylesterases: Cell Wall Remodeling Proteins Are Required for Plant Response to Heat Stress - Wu, Hui-Chen; Bulgakov, Victor P.; Jinn, Tsung-Luo (Frontiers in Plant Science, 2018)
Heat stress (HS) is expected to be of increasing worldwide concern in the near future, especially with regard to crop yield and quality as a consequence of rising or varying temperatures as a result of global climate change. HS response (HSR) is a highly conserved mechanism among different organisms but shows remarkable complexity and unique features in plants. The transcriptional regulation of HSR is controlled by HS transcription factors (HSFs) which allow the activation of HS-responsive genes, among which HS proteins (HSPs) are best characterized. Cell wall remodeling constitutes an important component of plant responses to HS to maintain overall function and growth; however, little is known about the connection between cell wall remodeling and HSR. Pectin controls cell wall porosity and has been shown to exhibit structural variation during plant growth and in response to HS. Pectin methylesterases (PMEs) are present in multigene families and encode isoforms with different action patterns by removal of methyl esters to influencing the properties of cell wall. We aimed to elucidate how plant cell walls respond to certain environmental cues through cell wall-modifying proteins in connection with modifications in cell wall machinery. An overview of recent findings shed light on PMEs contribute to a change in cell-wall composition/structure. The fine-scale modulation of apoplastic calcium ions (Ca2+) content could be mediated by PMEs in response to abiotic stress for both the assembly and disassembly of the pectic network. In particular, this modulation is prevalent in guard cell walls for regulating cell wall plasticity as well as stromal aperture size, which comprise critical determinants of plant adaptation to HS. These insights provide a foundation for further research to reveal details of the cell wall machinery and stress-responsive factors to provide targets and strategies to facilitate plant adaptation.